Diagnostic accuracy of ultrasound in common acute abdominal conditions - Deshmukh, Shashank; Kishan, A. Manmadha (International Surgery Journal, 2019)
Background: Ultrasound evaluation is cheap, easily available, even at rural level, and can predict need for surgical intervention in majority of conditions. It involves no exposure to radiation, can diagnose easily, can be repeated any number of times for follow up. Disadvantages are that it is user dependent and distended bowel containing air prevents satisfactory evaluation of abdomen. The objective was to study diagnostic accuracy of ultrasound in common acute abdominal conditions. Methods: All patients presenting to the emergency Department of General Surgery, Narayana general hospital, Nellore with abdominal pain of acute onset and who were diagnosed to be suffering from acute appendicitis, acute perforation peritonitis, acute intestinal obstruction, acute pancreatitis, acute calculous cholecystitis were included in the present study. Results: Diagnostic accuracy of USG for acute appendicitis was little bit low with sensitivity of 71.8% and specificity of 59.1% for operative findings and similar for CT findings. For acute perforation peritonitis it was still very low with sensitivity of 42.9% and specificity of 66.7% for operative findings and similar for CT findings. It was very good for acute intestinal obstruction with sensitivity of 90.9% and specificity of 83.3%, but here it was low compared to CT findings. It was also pretty good for diagnosing acute calculus cholecystitis in comparison with operative as well as CT findings. Conclusions: USG can be used as a diagnostic tool for diagnosis of acute intestinal obstruction and acute calculus cholecystitis but doubtful role in the diagnosis of acute appendicitis and acute perforation peritonitis and acute pancreatitis.